Grassland in Soil Conservation - Thakur, C. (Journal of Soil and Water Conservation, 2022)
Grass as a family ( Gramineae) in- cludes important food crops — rice, maize, millet, sugarcane, wheat, barley, oats, etc. It also includes the many species of crops which provide forages or pasture. But grass in the concept of grass- land agriculture is not limited to grasses; it also embraces their common associates of the legume family ( Leguminaceae ) the clovers, alfalfa and many others. Thus grassland agriculture differs from other types of farming chiefly with respect to the emphasis placed on grasses and legumes. They are dominant in a flexible pattern designed to conserve the land and its productivity but at the same time keep it adjustable to emergency needs.